2015
DOI: 10.1161/hypertensionaha.114.05010
|View full text |Cite
|
Sign up to set email alerts
|

First Report of the Global SYMPLICITY Registry on the Effect of Renal Artery Denervation in Patients With Uncontrolled Hypertension

Abstract: Abstract-This study aimed to assess the safety and effectiveness of renal denervation using the Symplicity system in realworld patients with uncontrolled hypertension (NCT01534299). The Global SYMPLICITY Registry is a prospective, open-label, multicenter registry. Office and 24-hour ambulatory blood pressures (BPs) were measured. Change from baseline to 6 months was analyzed for all patients and for subgroups based on baseline office systolic BP, diabetic status, and renal function; a cohort with severe hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
113
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 177 publications
(121 citation statements)
references
References 38 publications
6
113
0
Order By: Relevance
“…The beneficial myocardial effects of RDN were shown in the present study, whereas off‐target effects of RDN (eg, postprocedural blood pressure reduction, worsening renal function, and vascular complication) were also reported previously 35, 36. Therefore, careful patient selection should be clinically considered in the application of RDN.…”
Section: Discussionsupporting
confidence: 57%
“…The beneficial myocardial effects of RDN were shown in the present study, whereas off‐target effects of RDN (eg, postprocedural blood pressure reduction, worsening renal function, and vascular complication) were also reported previously 35, 36. Therefore, careful patient selection should be clinically considered in the application of RDN.…”
Section: Discussionsupporting
confidence: 57%
“…37, 38 The reduction in 24-h ambulatory SBP after RDN was less pronounced than the reduction in office SBP, in both OSA and non-OSA subjects, a phenomenon observed not only in the SYMPLICITY HTN-3 trial but in other studies of RDN. 38, 39 This difference in office and ambulatory BP reductions appears to be greater with increasing baseline BP. 40 Compared with 24-h ambulatory BP, office BP is more susceptible to white coat hypertension, Hawthorne effect, measurement bias, and measurement variability.…”
Section: Discussionmentioning
confidence: 97%
“…Greater BP-lowering effects occurred in patients with higher baseline pressures. [34] The recent results of the SYMPLICITY HTN-3 trial have challenged preclinical science, clinical anecdote, and the consistency observed across early phase trials. Although the trial demonstrated the safety of RSD, among 535 patients identified with treatment-resistant hypertension the difference in 6-month BP decline between RSD and sham-treatment groups was not significantly different for office or ambulatory measures.…”
Section: Discussionmentioning
confidence: 99%